2018
DOI: 10.4269/ajtmh.17-0593
|View full text |Cite
|
Sign up to set email alerts
|

Trypanosoma cruzi Infection Does Not Decrease Survival or Reproduction of the Common Bed Bug, Cimex lectularius

Abstract: Although not presently implicated as a vector of human pathogens, the common bed bug, , has been suspected of carrying human pathogens because of its close association with humans and its obligate hematophagy. Recently, we characterized the vectorial competence of for the parasite , the causative agent of Chagas disease. We observed that can acquire infection when fed on-carrying mice, and subsequently transmit to uninfected mice. This led us to ask why has not been implicated in the transmission of outside of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…The common bed bug, Cimex lectularius L., is an obligate hematophagous ectoparasite of humans [ 1 , 2 ] and one of the most challenging indoor pests to eradicate [ 1 , 3 ]. In contrast to many hematophagous arthropods that transmit pathogens to vertebrate hosts, bed bugs are believed not to transmit pathogens to humans [ 4 , 5 , 6 ], and have been shown to transmit pathogens to vertebrates only under controlled laboratory conditions [ 7 , 8 , 9 ]. The specific components of their innate immune system that bed bugs activate to eliminate pathogens or parasites are not known.…”
Section: Introductionmentioning
confidence: 99%
“…The common bed bug, Cimex lectularius L., is an obligate hematophagous ectoparasite of humans [ 1 , 2 ] and one of the most challenging indoor pests to eradicate [ 1 , 3 ]. In contrast to many hematophagous arthropods that transmit pathogens to vertebrate hosts, bed bugs are believed not to transmit pathogens to humans [ 4 , 5 , 6 ], and have been shown to transmit pathogens to vertebrates only under controlled laboratory conditions [ 7 , 8 , 9 ]. The specific components of their innate immune system that bed bugs activate to eliminate pathogens or parasites are not known.…”
Section: Introductionmentioning
confidence: 99%
“…Antiparasitic activity of various AMPs, such as BatxC, cecropin, crotalicidin, defensin a1138, dermaseptins, and mellitin, against T. cruzi has previously been demonstrated under laboratory conditions 16 , 31 , 52 54 . Results obtained in laboratory experiments suggested that T. cruzi may survive in the bed bugs’ midgut but is killed if it enters the hemocoel 27 , 29 . In our study, CL-prolixicn2 was expressed exclusively in the RoB—with no apparent up-regulation in the bed bugs’ midgut—suggesting that CL-prolixicin2 may not affect the development of T. cruzi in the midgut of bed bugs, but that it may inhibit T. cruzi, if it moves into the hemocoel.…”
Section: Discussionmentioning
confidence: 99%
“…The question whether bed bugs can transmit agents of human infectious diseases remains of great interest 22 25 . Many pathogens have been isolated from bed bugs 22 , 23 , 25 , 26 , and various parasites have been transmitted by bed bugs under laboratory conditions 23 , 27 29 . One such parasite is Trypanosoma cruzi , the etiological agent of Chagas disease, which causes premature heart failure of afflicted humans in the Americas.…”
Section: Introductionmentioning
confidence: 99%
“…This possibility has been suggested to explain why no cases of T. cruzi transmission by bed bugs have been documented. 42 Alternatively, because of differences in erythrolysis kinetics during the blood digestion process, the rate of pathogen shedding by bed bugs may be too low to naturally infect humans to any appreciable degree. 43 However, neither of these hypotheses has been investigated experimentally.…”
Section: Introductionmentioning
confidence: 99%